Degradasi Lahan dan Solusinya di Provinsi Riau, Indonesia - Elviriadi, Elviriadi; Siregar, M Sangap (Dinamika Lingkungan Indonesia, 2019)
Characteristic of Land degradation in Riau Province in the study can be viewed as any change or disturbance to the land perceived to be deleterious or undesirable area, loss of the biological and loss of natural vegetation, local economic productivity and complexity of rain-fed cropland, urban sprawl, irrigated cropland, forest and commercial development combination of processes arising from company/human activities. The conclusion was based on peat in Riau severe damage as a result of the drying system with the creation of canalization that followed the burning of forests and massive land over the last 17 years. As a result, a decline in Riau land of which 90% is the deepest tropical peat swamp in the world. Data analysis based on the results of the observation that has been going on for one year found severe damage to turf conditions Riau has been uneven in some areas. Damage to peat mainland Riau impact on the soil surface as is the case in Kalimantan, which is about 2 centimeters (cm) per year. Result and discussion revealed some of solutions to address the threat of damage due to the sinking of Riau burning peat. 1). “Rewetting” technique. 2) Back to traditional ecological knowledge management from the indigenous people. Whatever, this research refer for government to rseformation policy mindset; from the economic (oil palm plantation) oriented to promote the balance of nature and sustainability development.